A new species of Victoriopisa bantenensis (Crustacea: Amphipoda: Eriopisidae) from West Java, Indonesia - Arfianti, Tri; Wongkamhaeng, Koraon (Zootaxa, 2017)
Victoriopisa bantenensis sp. nov. has not been previously reported and also the first record of the genus in Indonesian waters. It was collected from soft-bottom subtidal sediment in Banten Bay, West Java, Indonesia and is one of two Victoriopisa which has a notch on the anteroventral margin of the head. Victoriopisa bantenensis is characterized by the absence of eyes, the lateral cephalic lobes elongate and the absence of excavation on the gnathopod 2 propodus palm. Male and female of Victoriopisa bantenensis sp. nov shows sexually dimorphic characters on gnathopods 2. Male gnathopod 2 propodus palm without excavation while female with one excavation. Previously, 13 species of Victoriopisa has been described, and this one is the 14 species of the genus.